Introduction to financial forecasting in investment analysis - Guerard, John B. (Springer, 2013)
With an emphasis on 'earnings per share' this data-oriented book covers financial forecasting, understanding financial data, strategies such as share buybacks and R&D spending, creating efficient portfolios and hedging stock holdings with financial futures